To be or not to be a carcinogen; delving into the glyphosate classification controversy (Brazilian Journal of Pharmaceutical Sciences, 2019)
The International Agency for Research on Cancer (IARC) placed the most widely used herbicide glyphosate (GLY) into the category 2A (probably carcinogenic to humans), a classification questioned by experts from academia and industry. This article critically appraised the epidemiological and experimental data that led the IARC working group (WG) to consider GLY a probable human carcinogen and the ensuing controversy. An association of GLY with non-Hodgkin lymphoma was suggested by some observational studies. A non-causal explanation for this weak association, however, cannot be excluded. Contrary to WG’s view, long-term rodent assays yielded no convincing evidence that GLY is carcinogenic. The mechanistic evidence remains elusive as well. Bacterial reverse mutation tests (including tester strains sensitive to oxidative mutagens) were clearly negative, and so were rodent genotoxicity assays by oral route. Tests with mammalian cells in vitro yielded conflicting results at high (cytotoxic) concentrations of GLY-based formulations. Conflicting results were also obtained when high doses of GLY-based herbicides were administered to rodents by the intraperitoneal route. Such high doses are unlikely to be attained in realistic scenarios of exposure. Finally, the IARC classification is based on a conjectural hazard, and rational public health interventions must be based on estimated risks.